Digital Twin Development for the Automotive Industry - Sheladiya, Chirag; Shafighi, Najla; Hajibashi, Anahita Amini (Archives of Business Research, 2024)
This study explores Digital Twin Development for the Automotive Industry which aims to bridge the divide between automotive and digital engineering. Results, which were analyzed using demographic and regression analyses, indicate that there are significant correlations between control accuracy and protection level, but not with data integrity and privacy, and real-time monitoring effectiveness.